Response of tidal dynamics and shear fronts to topographic changes in the Yellow River Delta - Dong, Fengjiao; Han, Shuzong; Su, Hanxiang; Wu, Dexing; Liang, Xiaohong (Frontiers in Marine Science, 2024)
In recent years, the position of the Yellow River Estuary (YRE) entrance has changed frequently, and human activities such as land reclamation have contributed to the transformation of the deltaic topography. These combined factors have resulted in altered hydrodynamics and tidal shear fronts (TSFs) in the surrounding sea area. However, there are few studies on the characteristics of the TSFs before and after diversion, so this paper establishes a hydrodynamic model based on the Finite Volume Coastal Ocean Model (FVCOM) for the years 2005, 2014, and 2020 and analyzes the characteristics of the changes in the tidal currents and the TSFs before and after diversion and the long-term evolution trends. The results reveal that the M2 amphidromic point near the YRE shifted eastward by 4.9 km from 2005 to 2014 and migrated southeastward by 6.8 km between 2014 and 2020. Additionally, significant changes were observed in the maximum and residual currents within the active mouth (AM), the old Qing 8 (Q8) channel, the old QingShuiGou (QSG) channel, and the southeastern region. Notably, the residual currents exhibit vertical fronts with substantial current velocity differences across the slopes. After the diversion of the YRE, the northern TSFs disappeared. The TSFs in the AM gradually shifted landward, while the TSFs in the southeastern region shifted offshore. In the vertical direction, the frontal centerlines of the TSFs gradually moved offshore from top to bottom. The intensity of the TSFs at the same latitude was positively correlated with the offshore distance. Generally, steeper slopes were associated with larger bottom stress gradients, which in turn corresponded to stronger TSFs.